A Phase I, Open-label, Dose-escalation, and Cohort Expansion Study to Evaluate the Safety and Immune Response to Autologous Dendritic Cells Transduced With AdGMCA9 (DC-AdGMCAIX) in Patients With Metastatic Renal Cell Carcinoma. Issue 9 (November 2020) - Faiena, Izak; Comin-Anduix, Begoña; Berent-Maoz, Beata; Bot, Adrian; Zomorodian, Nazy; Sachdeva, Ankush; Said, Jonathan; Cheung-Lau, Gardenia; Pang, Jia; Macabali, Mignonette; Chodon, Thinle; Wang, Xiaoyan; et al.
Abstract : Expression of carbonic-anhydrase IX (CAIX) in clear cell renal cell carcinoma (RCC) makes it an attractive vaccine target. We developed a fusion-gene construct, granulocyte-macrophage (GM) colony-stimulating factor+CAIX, delivered by an adenoviral vector (Ad) into autologous dendritic cells (DCs) in this phase 1 study. The injected immature DCs were expected to stimulate an antigen-specific immune response against CAIX expressing RCC. Three dose-escalation cohorts (5, 15, and 50×10 6 cells/administration) were injected intradermally q2wk×3 doses based on a 3+3 design. The primary objective was the safety of the injections. Secondary objectives were immune responses using enzyme-linked immunosorbent spot, a serum biomarker panel, and clinical response. Fifteen patients with metastatic RCC were enrolled, and 9 patients received all 3 doses. No serious adverse events were seen. There were 3 (33%) patients with grade 1 fatigue, 1 of whom subsequently experienced grade 2 fatigue. One patient (11%) experienced grade 1–2 leukopenia. Only 1 patient (11%) experienced grade 2 flu-like symptoms. Of the 9 patients who received treatment, 1 expired of progressive disease, 2 patients were lost to follow-up and 6 patients are alive. Of the 6 patients, 5 have progressive disease, and 1 has completed treatment with stable disease at 27 months follow-up. Immune response measurements appeared more robust in higher dose cohorts, which appeared to be related to patients with stable disease at 3 months. These early data show that autologous immature DC-AdGMCAIX can be safely given to metastatic RCC patients without any serious adverse events with CAIX-specific immune response elicited by the treatment. These preliminary data support further study of Ad-GMCAIX, particularly with combination therapies that may enhance clinical activity. Abstract : Supplemental Digital Content is available in the text.